2006
DOI: 10.1103/physreva.74.053808
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic intensity fluctuations in random lasers

Abstract: We present a quantitative experimental and theoretical study of intensity fluctuations in the emitted light of a random laser that has different realizations of disorder for every pump pulse. A model that clarifies these intrinsic fluctuations is developed. We describe the output versus input power graphs of the random laser with an effective spontaneous emission factor ͑␤ factor͒.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 19 publications
0
56
1
Order By: Relevance
“…-focus area A of the pump beam on the sample, as it provides information of the size and shape (together with ℓ and ℓ a ) of the amplified volume -wavelength of the pump laser λ p -duration of the pump pulse t p , as studies have shown that pulse duration is an important parameter [4,20] -repetition rate of the pump laser -pump fluence I for every published spectrum -integration time for every published spectrum Before we list the required experimental data, we briefly elaborate on two key criteria: the occurrence of spikes and gain narrowing. The occurrence of spikes in an emission spectrum of a random laser is a central issue.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…-focus area A of the pump beam on the sample, as it provides information of the size and shape (together with ℓ and ℓ a ) of the amplified volume -wavelength of the pump laser λ p -duration of the pump pulse t p , as studies have shown that pulse duration is an important parameter [4,20] -repetition rate of the pump laser -pump fluence I for every published spectrum -integration time for every published spectrum Before we list the required experimental data, we briefly elaborate on two key criteria: the occurrence of spikes and gain narrowing. The occurrence of spikes in an emission spectrum of a random laser is a central issue.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In this paper, we address the question whether the lasing modes are the quasimodes of passive random systems. The answer to this question determines whether the statistical distribution of the decay rates of quasimodes can be used to predict the lasing threshold and the number of lasing modes for random laser 12,13,14,15,16,17,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…From the solution of the diffusion equation, the mean value of the cavity-decay time t c can be derived 27 and found to depend on D(l), t c ¼ L 2 /8D(l). From equation (1) it is then evident that the threshold and laser process can be controlled by modifying D(l) and hence ' t (l).…”
mentioning
confidence: 99%
“…In previous work 9, 27 , spheres or particles have always been dispersed in a solvent plus laser dye, making the refractive index contrast very low. This meant that at the given values of polydispersity it was impossible to resolve any Mie resonances.…”
mentioning
confidence: 99%